Formalization of basic transformations models of evolutionary computing - P.P. Makarychev; N.V. Sleptsov (Известия высших учебных заведений. Поволжский регион:Технические науки, 2024)
Background. An approach to the formalized representation of models of genetic algorithms as a kind of evolutionary calculations is proposed. The issues of data representation to improve the efficiency of evolutionary search, the choice of operations in the formalized representation of genetic transformations and the construction of mathematical models of calculations are discussed. It is noted that the organization of evolutionary calculations within the framework of the most common varieties of genetic algorithms leads to the need for a formalized representation of a sufficiently large set of parameters that affect the efficiency of the process of evolutionary calculations in relation to a specific task. Two approaches to the task of binary representations are considered. The first approach assumes a binary representation, the second approach assumes a binary encoded representation. Models for unlimited and restricted populations providing the use of a wide range of transformation and selection operators are discussed. The proposed approach is most effective in solving the problem of evolutionary calculations, taking into account the maximization of key patterns. Results. The theoretical substantiation of the structure and parameters of models of evolutionary calculations for solving problems of identification and forecasting of the state of technical objects and socio-economic systems is carried out. Conclusions. The proposed approach provides a formalized description of the basic transformations for models of evolutionary calculations with limited and unlimited populations. The approach can be used in the formalized formulation of the problem of maximizing key patterns in an evolving model.